2015
DOI: 10.1177/1074248415617850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Reperfusion Pressure on “No Reflow” Area and Infarct Size in a Porcine Model of Ischemia–Reperfusion

Abstract: Modestly elevated blood pressure during reperfusion is associated with an increase in no reflow area and in infarct size in a clinically relevant porcine model of ischemia-reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…202 In contrast, partial clamping of the aorta to increase perfusion pressure augmented infarct size and no-reflow in pigs. 203 Hypothermia (32°C) in rats and rabbits undergoing 30-minute coronary occlusion and reperfusion reduced infarct size and no-reflow area when initiated shortly after the onset of myocardial ischemia. 204 Of note, whereas in rabbits undergoing 30-minute coronary occlusion with reperfusion, topical hypothermia (32°C) when initiated at 5 minutes before versus at 5 minutes after reperfusion tended to reduce infarct size only with hypothermia started before reperfusion, the area of no-reflow was reduced in both cases.…”
Section: Interventionsmentioning
confidence: 99%
“…202 In contrast, partial clamping of the aorta to increase perfusion pressure augmented infarct size and no-reflow in pigs. 203 Hypothermia (32°C) in rats and rabbits undergoing 30-minute coronary occlusion and reperfusion reduced infarct size and no-reflow area when initiated shortly after the onset of myocardial ischemia. 204 Of note, whereas in rabbits undergoing 30-minute coronary occlusion with reperfusion, topical hypothermia (32°C) when initiated at 5 minutes before versus at 5 minutes after reperfusion tended to reduce infarct size only with hypothermia started before reperfusion, the area of no-reflow was reduced in both cases.…”
Section: Interventionsmentioning
confidence: 99%
“…This may be due to the failure of the thrombolytic or no-reflow effect. According to previous research [ 44 , 45 ], multiple factors, including microvascular obstruction, edema, and occlusion via the endothelium, could cause the no-reflow effect, even though the primary occlusion was resolved. Owing to this phenomenon, the tissue was unable to receive the nutritional support needed to recover sustainably, which might lead to more severe brain damage and a higher mRS score.…”
Section: Discussionmentioning
confidence: 99%
“…When aortic pressure was increased by ˜20% over baseline, both the infarct area and the area of no-reflow were increased relative to control experiments. 197 Takeo et al observed that an optimal reduced perfusion flow rate to maximize left ventricular function could be found, though the translational value of the precise flow rate is limited as the work was performed in isolated rat hearts. 195 Similarly working in an isolated rat heart model, Nemlin et al found an optimal pressure for LPR of 51 mmHg (whereas normal pressure was 73 mmHg).…”
Section: Controlled Reperfusionmentioning
confidence: 99%